Effect of blood lead levels on periodontitis in American adults: a cross-sectional analysis from the national health and nutrition examination survey - Tangye Dai; Qun Dai (BMC, 2024)
Abstract Background The primary objective of this study was to assess the impact of blood lead levels on the development and progression of periodontitis. Methods This study included 8600 participants from the National Nutrition and Health Examination Survey conducted the United States between 2009 and 2014. The exposure variable was the blood lead level, while the outcome variable was periodontitis. To evaluate the relationship between the blood lead level and periodontitis, a multivariate logistic regression model was used. Results A positive association was observed between blood lead levels and the risk of periodontitis in Model 1 (OR = 7.04, 95% CI = 5.95-8.31). After adjusting for age (continuous), sex, ethnicity, and BMI (continuous) in Model 2, the significant association between blood lead levels and periodontitis risk remained evident (OR = 3.06, 95% CI: 2.54-3.70). Consequently, even after comprehensive adjustment for potential confounding factors in Model 3, the robust association between blood lead levels and periodontitis risk persisted (OR = 2.08, 95% CI = 1.67-2.60). When considering the serum lead concentration as a categorical variable and after adjusting for potential confounders in Model 3, we observed that the odds ratios (ORs) of periodontitis in the T2 (0.94 µg/dL-1.60 µg/dL) and T3 (lead ≥ 1.60 µg/dL) groups increased from 1.27 (OR = 1.27, 95% CI: 1.11-1.44) to 1.57 (OR = 1.57, 95% CI: 1.36-1.81) compared to T1 group. Subgroup analysis revealed no effect modifiers. Conclusions Our main findings suggest that there is no safe range of blood lead levels regarding periodontitis risk and that increasing blood lead levels can significantly increase the prevalence of periodontitis.